2017
DOI: 10.1155/2017/1254792
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Dextran Sedimentation as an Initial Step in Neutrophil Purification Promotes Their Stimulation, due to the Presence of Monocytes

Abstract: The purification of human neutrophils for in vitro studies is challenging as they are easily activated through ex vivo manipulations. The technique of erythrocyte sedimentation combined with density gradient centrifugation remains widely practiced and was the subject of this study. Since in the sedimentation step the leukocytes are incubated with dextran, we have raised the likelihood that cellular activation would occur with mediator release leading to neutrophil activation. By comparing the activity of neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…RT-DC is an imaging flow cytometer where bright-field images of cells in flow are captured by a high-speed camera ( Figure 3A) at rates of 100 -1,000 cells/s. In order to increase the frequency of leucocytes, whole blood was first depleted from RBCs by dextransedimentation (Bøyum, 2008;Quach and Ferrante, 2017). As recently published by Toepfner et al, the individual cell populations can be identified simply by considering cross-sectional area and brightness, calculated as the average grayscale value of all pixels belonging to the cell ( Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…RT-DC is an imaging flow cytometer where bright-field images of cells in flow are captured by a high-speed camera ( Figure 3A) at rates of 100 -1,000 cells/s. In order to increase the frequency of leucocytes, whole blood was first depleted from RBCs by dextransedimentation (Bøyum, 2008;Quach and Ferrante, 2017). As recently published by Toepfner et al, the individual cell populations can be identified simply by considering cross-sectional area and brightness, calculated as the average grayscale value of all pixels belonging to the cell ( Figure 3B).…”
Section: Resultsmentioning
confidence: 99%
“…To prepare RBC-depleted blood samples, 2 mL of a 6% dextran solution (Dextran T500, Pharmacosmos A/S, Denmark) diluted in sodium chloride (0.9% Sodium Chloride Irrigation, Baxter Healthcare, Switzerland) was added to 10 mL of whole citrated blood. After gentle mixing, RBCs were allowed to sediment for 30 min (Bøyum, 2008;Quach and Ferrante, 2017). The supernatant was transferred to a 10 mL tube and centrifuged for 10 min at 120 g (Universal 30RF, Hettich, Switzerland).…”
Section: Real-time Fluorescence and Deformability Cytometry For Bloodmentioning
confidence: 99%
“…We also need to keep in mind that the pathways engaged in NETosis can be influenced by the state of priming and pre-activation of neutrophils due to the techniques of purification. 124,125…”
Section: F I G U R Ementioning
confidence: 99%
“…Similar to macrophage phagocytosis of C. albicans, uptake of isolated fungal zymosan A is more efficient in opsonising conditions, with phagocytosis after a 15-min incubation time being three times higher in reactions with complement compared to no serum and heat-inactivated serum controls (Figure 1). were prepared from human peripheral blood from healthy volunteers, using the high density gradient method [17].…”
Section: Using Commercially Available Labelled Zymosan a Bioparticlesmentioning
confidence: 99%